OC 8546 Safety and immunogenicity of the malaria vaccine candidate BK-SE36 in young children living in burkina faso. (24th April 2019) - Sirima, Sodiomon; Tiono, Alfred B; Houard, Sophie; Bougouma, Edith C; Coulibaly, Sam A; Leroy, Odile; Palacpac, Nirianne; Horii, Toshihiro; Ouedraogo, Issa N
Abstract : Background: The malaria blood stage vaccine candidate SE-36 is based on the serine repeat antigen of Plasmodium falciparum . Epidemiological studies have shown that antibodies against SE36 correlate with lower parasitaemia in Solomon Island residents. In a phase I b trial conducted in Uganda, the BK-SE36 vaccine, SE36 formulated with aluminium hydroxide gel, was found safe and immunogenic. Interestingly, highest levels of IgG anti-SE36 protein associated with protection against severe malaria were found in the youngest Ugandan trial participants. Objectives: To assess the safety and immunogenicity of the BK-SE36 vaccine in a randomised controlled double-blind age de-escalating phase Ib clinical trial in younger (≤5 years) malaria-exposed children living in Burkina Faso. Methods: Healthy participants (108) were included in two age cohorts, one consisting of 54 children aged 25–60 months and the other of 54 children aged 12–24 months. Trial participants received 3 intramuscular or subcutaneous injections of the BK-SE36 vaccine at Day 0, Week 4 and 26. Participants allocated to the control group received the control Synflorix vaccine via intramuscular route at Day 0 and Week 26 and saline at Week 4. The participants were followed for one year. Immune responses were evaluated by ELISA, ELISpot and parasite carriage by microscopy and PCR. Results: Preliminary data from an interim analysis (data collected one month after the last immunisation) indicated that the vaccine was safe, well-tolerated and induced an IgG anti-SE36 response in these younger populations. The trial's latest safety, immunogenicity and preliminary efficacy results will be presented.